2017
DOI: 10.1016/j.clinthera.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Schemas in Placebo and Nocebo Responding: Role of Autobiographical Memories and Expectations

Abstract: The adapted tasks for assessing cognitive (memory and expectations) schemas on itch seem promising in explaining interindividual differences in placebo itch responding. Future research should investigate whether similar mechanisms apply to patients with chronic itch. This knowledge can be used for identifying patients who will benefit most from the placebo component of a treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Nevertheless, as mentioned elsewhere, numerous studies reveal that expectancies also modulate placebo and nocebo effects (Bartels et al, 2014; Bartels, van Laarhoven, Heijmans, et al, 2017; Bartels, van Laarhoven, Stroo, et al, 2017; Bingel et al, 2011; Bräscher, Witthöft, & Becker, 2018; Fiorio et al, 2012). Expectancies are induced by verbal instructions, social observation (for reviews see, Colloca & Grillon, 2014; Medoff & Colloca, 2015) and distinct forms of learning (for example, Benedetti et al, 2003; Egorova et al, 2015; Morton, El-Deredy, & Jones, 2014; Reicherts, Gerdes, Pauli, & Wieser, 2016).…”
Section: Role and Manipulation Of Expectanciesmentioning
confidence: 85%
“…Nevertheless, as mentioned elsewhere, numerous studies reveal that expectancies also modulate placebo and nocebo effects (Bartels et al, 2014; Bartels, van Laarhoven, Heijmans, et al, 2017; Bartels, van Laarhoven, Stroo, et al, 2017; Bingel et al, 2011; Bräscher, Witthöft, & Becker, 2018; Fiorio et al, 2012). Expectancies are induced by verbal instructions, social observation (for reviews see, Colloca & Grillon, 2014; Medoff & Colloca, 2015) and distinct forms of learning (for example, Benedetti et al, 2003; Egorova et al, 2015; Morton, El-Deredy, & Jones, 2014; Reicherts, Gerdes, Pauli, & Wieser, 2016).…”
Section: Role and Manipulation Of Expectanciesmentioning
confidence: 85%
“…Previous studies regarding nocebo effects on itch have found indications for a role of psychological characteristics in relation to negative outcome expectancies, like worrying or negative affect, however research is extremely scarce [ 50 ]. Moreover, in a recent study by our research group, indications were found that one’s cognitive schemas regarding specificity and valence of memories and expectations regarding itch are related to placebo responding on itch, i.e., participants who were more specific in their memories regarding itch and who had less negative itch-related expectations for the future were more likely to be placebo itch responders [ 33 ]. Future research should further investigate the determinants of (reversing) nocebo responses, like individual differences in psychological characteristics in relation to negative outcome expectancies and cognitive schemas regarding memories and expectations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we exploratively tested the extent to which previously reduced nocebo effects would generalize to a different itch stimulus to assess external validity. Furthermore, it was explored whether psychological characteristics related to negative or positive outcome expectancies (e.g., worrying or optimism, respectively) were associated with (reversion of) nocebo responses [ 15 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Appendix Table 2 Environmental factors and stimuli modifying placebo/nocebo effects Modifiable Non-modifiable Patient's expectations [13] Previous experiences [14] Pre-treatment verbal and non-verbal suggestions [15,16] Patient's personality [17] Speed of treatment titration [18] Cultural factors [19,20] Safety profile of treatment [21] Age [22] Patient-doctor relation/communication [23] Social Media and Internet information [24] Investigator/physician status [15] Gender [25] Affective and cognitive traits [26] Level of patients' education [22] Generic formulations [27,28] Genetics [29] The appearance of drugs or medical devices, e.g. packaging, color, price, drug taste, etc.…”
Section: Fundingmentioning
confidence: 99%